Organic paddy (Oryza sativa L.) production / Siti Atikah Salip - Salip, Siti Atikah (Faculty of Plantation and Agrotechnology, 2016)
In this review paper, the ways to produce organic paddy by applying appropriate organic matters without using synthetic fertilizers are discussed. The pest and disease control by biological method is also presented. Application of herbicides and all chemical substances is prohibited in uses. Organic paddy production gives benefits to the farmers and consumers in two ways, which are lower management cost with the use of organic fertilizer based on waste substances and improved environmental quality. The environmental damage attributed to methane gas emission into the air by conventional paddy cultivation practices is also covered in this paper. Methane gas emission is well known as a greenhouse gas that causes global warming problem.